APPLICATION OF DECISION SUPPORT SYSTEM FOR DETERMINING AMPHIBIOUS LANDING BEACH IN WEST PAPUA INDONESIA - Budi Setiarso; Udisubakti Ciptomulyono; Bambang Suharjo; I Nengah Putra; A K Susilo (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2018)
ABSTRACT Determination of the landing beach becomes a must for the Marine Forces of the Indonesian Navy as an element of the landing forces in order to carry out the task of amphibious operations in particular to determine the ideal landing beach location for the successful implementation of the task. Requirements on the determination of ideal landing beaches should be in accordance with predetermined parameters and serve as an important component in determining the weighting value of landing beach selection criteria. This study aims to determine the location of landing beaches by using the Preference Ranking Method Method of Organization for Enrichment Evaluation (PROMETHEE) combined into the Borda method. The research stages started from determining the value of criterion preferences to the landing beach alternative options analyzed by PROMETHEE method then processed again in Borda method. The PROMETHEE method is used to analyze individual decisions of decision makers, while the Borda method is used to manage group decisions from the PROMETHEE method of ranking. The use of both methods is a solution to generate more objective group decisions so as to obtain a ranking result against the selection of logical amphibious landing beaches and have an objective value in accordance with accurate data and greatly assist decision-makers to solve multi-criteria problems. From the results of this study can be seen that the location of the selected beach is the most feasible to serve as the location of landing beaches in amphibious operations is Beach 3 with a weighted value of 0.389. Keywords: Amphibious operations, the landing beach, Decision Support Systems, PROMETHEE, Borda